A study of eco-performance of logistics services in food supply chains - Li, Dong; Hanafi, Zurina (AASMR, 2013)
Transportation is one of the main contributors of greenhouse gases which give direct negatives impact on environment.Management of logistics services plays an important role in maintaining business competitiveness and sustainability as well as social responsibility.Optimizing logistics service with integrated economic and ecological objectives can help to reduce negative impact on the environment by reducing the amount of carbon emissions and improving operations efficiency. This study focuses on multimodal transportation planning and optimal strategies with a UK food supply chain case under carbon emissions control policies.Carbon emissions policy is a driving factor for multimodal transportation planning in ecologistics management.With differences in the level of carbon emissions control, the different characteristics of the cost structure and carbon emission in different logistics processes will lead to different business performance. The research investigates and identifies impact of the policies on logistics performance.